Teaching integrated skills through the BookWidgets web - Kelvin Rahmana Jaya Mendrofa; Dirman Yanto Zamago; Syukur Pebriman Gulo; Joel Kristiawan Gea; Fersi Gea; Ryan Memories Harefa; Indi Yarnila Nazara; Yasminar Amaerita Telaumbanua (CV. Literasi Indonesia, 2026)
The rapid development of educational technology requires pre-service English teachers to possess digital pedagogical competencies that support the implementation of technology-enhanced learning. However, many students are still unfamiliar with digital learning platforms such as BookWidgets and have limited experience in designing integrated English language learning activities. This community service program aimed to introduce the BookWidgets platform and improve participants' ability to develop integrated English learning activities involving reading, writing, listening, and speaking skills. The program was conducted on June 8, 2026, involving ten students from the English Language Education Study Program at Universitas Nias. The implementation consisted of platform demonstrations, guided hands-on practice, observation, documentation, and evaluation through a post-training questionnaire. The findings showed that most participants successfully designed integrated language learning activities using BookWidgets for English language teaching. Although several technical challenges, including unstable internet connectivity and Gmail account access issues, were encountered, these obstacles were successfully addressed through direct facilitation and continuous guidance. The program demonstrates that practical training using BookWidgets effectively strengthens the digital pedagogical competence of pre-service English teachers and supports the integration of technology into English language teaching.